Emerging areas of opioid pharmacology. (22nd June 2018) - Kelly, Eamonn; Henderson, Graeme; Bailey, Chris P
Abstract : This themed section of the British Journal of Pharmacology stems from an International Narcotics Research Conference (INRC) meeting held in July 2016 at The Assembly Rooms in Bath, UK. Linked Articles: This article is part of a themed section on Emerging Areas of Opioid Pharmacology. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.14/issuetoc